Etiology Based and Stage-Adapted Management of Hemorrhoidal Disease: Clinical Outcomes, Functional Impact, and Quality of Life — A Narrative Review - Tabor, Zuzanna (Quality in Sport, 2026)
Background: Hemorrhoidal disease is a highly prevalent anorectal condition impacting quality of life and functional capacity. Modern understanding highlights a complex interplay of mechanical, vascular, and inflammatory pathologies. Optimal management demands an etiology- and stage-specific approach. Aim: This narrative review aims to integrate current evidence on the etiology, pathophysiology, and classification of hemorrhoidal disease to evaluate therapeutic strategies. It focuses on correlating treatment efficacy, recurrence rates, and functional outcomes with specific disease stages, including their impact on patient quality of life and engagement in active lifestyles. Material and methods: A comprehensive literature search was conducted using PubMed, PubMed Central (PMC), MEDLINE, Embase, and the Cochrane Library for studies published between 2015 and 2025. Selected articles focused on hemorrhoid etiology, staging, and both physical and psychological treatment outcomes. Results: Hemorrhoidal disease progresses from vascular congestion (Grade I-II) to significant connective tissue failure (Grade III-IV). Conservative and office-based interventions effectively manage early vascular-dominant disease with minimal downtime. Minimally invasive surgical techniques balance efficacy with reduced morbidity for mixed vascular-structural pathologies (Grade III). Excisional hemorrhoidectomy remains the definitive treatment for severe structural collapse (Grade IV), offering the lowest recurrence. Treatment success, measured by physical relief and high patient-reported quality of life, strongly correlates with precise stage- and etiology-matched therapy, facilitating return to active lifestyles. Conclusions: A tailored, etiology- and stage-adapted approach to hemorrhoidal disease management is crucial for optimizing clinical outcomes, preventing recurrence, and enhancing patient functional status and psychological well-being.